Codon-based mutagenesis using dimer-phosphoramidites. - Neuner, P (1998)
A new approach for the synthesis of randomized DNA sequences containing the 20 codons corresponding to all natural amino acids is described. The strategy is based on the use of dinucleotide phosphoramidite building blocks within a resin-splitting procedure. Through this protocol, a minimal number of seven dimers is sufficient to encode all 20 natural amino acids. This synthesis procedure is extremely flexible and allows codon usage from different hosts to be accommodated.